1995
DOI: 10.1002/neu.480260202
|View full text |Cite
|
Sign up to set email alerts
|

A direct comparison of the masculinizing effects of testosterone, androstenedione, estrogen, and progesterone on the development of the zebra finch song system

Abstract: To assess which hormones are capable of masculinizing the neural song system of zebra finch hatchlings, we implanted female hatchlings with estrogen (estradiol [E2], 75 micrograms, n = 9), testosterone (T, 75-88 micrograms, n = 13), androstenedione (AE, 75 micrograms, n = 7), progesterone (P, 117 micrograms, n = 10), or nothing (Blanks, n = 10) and compared these to unimplanted males (n = 7). Implants, consisting of a hormone and Silastic mixture encased in polyethylene tubing, were placed under the skin of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 37 publications
1
52
0
Order By: Relevance
“…This sex difference results from dramatic sex differences in the neural circuit responsible for this behavior. Males have larger song nuclei that have larger neurons and make interconnections that are either absent or vestigial in females [9,19,23,26,31]. Sex differences in androgen accumulation or androgen receptor expression are found in song regions HVC and lMAN [4,7,24] and to a lesser extent in RA and Area X [2,18]; in these areas, males express more androgen receptors than females do.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sex difference results from dramatic sex differences in the neural circuit responsible for this behavior. Males have larger song nuclei that have larger neurons and make interconnections that are either absent or vestigial in females [9,19,23,26,31]. Sex differences in androgen accumulation or androgen receptor expression are found in song regions HVC and lMAN [4,7,24] and to a lesser extent in RA and Area X [2,18]; in these areas, males express more androgen receptors than females do.…”
Section: Introductionmentioning
confidence: 99%
“…Administering estradiol to hatchling females masculinizes their song systems [9,11,14] and up-regulates the expression of androgen receptors in HVC, Area X, and lMAN [18,25]. Additionally, co-administering flutamide, an androgen receptor antagonist [22,27], with estradiol markedly blocks estradiol's ability to masculinize the female song system [11], suggesting that activation of androgen receptors is a necessary step for the masculinization of the song system-at least in estrogenized female hatchlings.…”
Section: Introductionmentioning
confidence: 99%
“…By the mid-1980s, the applicability of the mammalian view to zebra finches was based primarily on three findings: (1) Treatment of hatchling female zebra finches with estrogen causes dramatic masculinization of the neural song circuit, and such estrogenized females sing as adults. Indeed, this finding has been replicated in several laboratories, and is the strongest evidence for the mam malian theory le.g., Gurney, 1981;Konishi and Akutagawa, 1988;Simpson and Vicario, 1991;Adkins-Regan cl al., 1994;Grisham and Arnold, 1995;Jacobs et al, 1995], (2) Nonaromatizable androgens such as DHT, which are products of the testes, also have distinct mas culinizing properties, but they are less dramatic than those of estrogen [Gurney, 1981 Estrogen treatment of hatchling females causes an increase in accumulation of androgen in specific regions of the song system [Nordeen et al, 1986], Since females masculin ized at hatching with estrogen were thought to be further masculinized by treatment with androgens in adulthood [Gurney and Konishi, 1980], it was suggested that full masculinization of the neural song system required estro gen and androgen action. The need for both types of steroid action corresponded closely to the pattern of steroid action in mammals, especially rats, and was therefore attractive.…”
Section: Reexamination Of the Applicability Of The Mammalian Hypothesismentioning
confidence: 99%
“…Early investigations of the mechanisms regulating sexual differentiation focused on E2; treating hatchling females with this hormone can both masculinize the anatomy of their song circuits and allow them to produce some song in adulthood (figure 1). However, complete masculinization does not occur [12]. If E2 does normally masculinize males, then some mechanism should exist to increase its availability or activity in this sex, but oestrogen receptors in the song system appear limited overall and comparable in males and females.…”
Section: Songbirdsmentioning
confidence: 99%